2021
DOI: 10.4014/jmb.2007.07013
|View full text |Cite
|
Sign up to set email alerts
|

The First Report to Evaluate Safety of Cyanobacterium Leptolyngbya sp. KIOST-1 for Use as a Food Ingredient: Oral Acute Toxicity and Genotoxicity Study

Abstract: Leptolyngbya sp. KIOST-1 (LK1) is a newly isolated cyanobacterium that shows no obvious cytotoxicity and contains high protein content for both human and animal diets. However, only limited information is available on its toxic effects. The purpose of this study was to validate the safety of LK1 powder. Following Organisation for Economic Co-operation and Development (OECD) guidelines, a single-dose oral toxicity test in Sprague Dawley rats was performed. Genotoxicity was assessed using a bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…This strain demonstrated biomass productivity, a high protein content, and an amino acid composition comparable to A. maxima, with no observed cytotoxicity [12]. Moreover, subsequent research identified no putative cyanotoxin genes, and the dried biomass did not exhibit acute toxicity in experimental animals [13,14]. These results suggest that Leptolyngbya sp.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…This strain demonstrated biomass productivity, a high protein content, and an amino acid composition comparable to A. maxima, with no observed cytotoxicity [12]. Moreover, subsequent research identified no putative cyanotoxin genes, and the dried biomass did not exhibit acute toxicity in experimental animals [13,14]. These results suggest that Leptolyngbya sp.…”
Section: Introductionmentioning
confidence: 81%
“…Previous studies have reported that Leptolyngbya sp. KIOST-1 has a high protein content and no cytotoxicity, cyanotoxin-related genes, or acute toxicity, suggesting that it may be a potential protein source candidate [12][13][14]. In this study, we attempted to determine the fundamental physiological characteristics of this species necessary for its cultivation to produce biomass.…”
Section: Discussionmentioning
confidence: 99%